Reducibility of linear systems of difference equations with almost periodic coefficients - Martynyuk, D. I.; Mitropolskiy, Yu. A.; Tynnyi, V. I. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
For the linear systemof difference equations x(t + 1) = Ax(t) + P(t)x(t), where the matrix P(t) is almost periodic, sufficient conditions are given, which reduce it to a system with a constant matrix.